INFORMATIKA PÁNIN OQITIWDA QOLLANILATUǴIN INTERAKTIV PROGRAMMALAR HÁM WEB-SAYTLARDIŃ ABZALLIQLARI - Orinbayeva, A. (SCIENCE and SOCIETY, 2023)
The article mentions the benefits and processes of developing interactive applications and websites used by computer science teachers in higher education institutions.